GRAVITATIONAL LENSING BY GLOBULAR CLUSTERS. INFLUENCE OF MICROLENSING - Yushchenko, A. V.; Niarchos, P. G.; Terpan, S.; Manimanis, V. (Одеські астрономічні публікації, 2017)
Quasar-galaxy associations can be explained as gravitational lensing by globular clusters, located in the halos of foreground galaxies. We propose new observational test for checking this hypothesis. We used SUPERCOSMOS sky survey to find over-densities of star-like sources with zero proper motions in the vicinities of foreground galaxies from CfA3 catalog. Preliminary results show that our hypothesis is true. We discuss the in of microlensing on the results of observations. We made CCD VRI photometry on 1.22 meter telescope of Kryonerium observatory (Greece) to select extremely lensed objects around 6 galaxies.